Predicting Turnover Intention Through Employee Satisfaction and Organizational Commitment in Local Banks in East Java - Eko Nurtjahjono, Gunawan; Setyono, Langgeng; Happy Sugiastuti, Reika; Jihad Fisabilillah, Rizaldi (FIA UB, 2023)
An organisation is required to apply Job Satisfaction to maintain productivity in improved operations. The purpose of this study is to learn how Organizational Commitment mediates the effect of Job Satisfaction on Turnover Intentions, and then to find out whether Job Satisfaction influences Turnover Intention and Organizational Commitment influences Turnover Intention. This type of research is quantitative, with a population of all employees of PT. Bank Pembangunan Daerah Jawa Timur, Malang City branch, using a stratified random sampling method with a sample of 113 respondents. Data analysis using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS software. The results of the study showed that Job satisfaction has a significant effect on Organizational Commitment. Job satisfaction has a significant effect on Turnover IntentiOrganisationalonal commitment has a significant effect on Turnover Intention. Organisational commitment partially demonstrates a significant influence in mediating job satisfaction on the Turnover Intention of employees of PT. Bank Pembangunan Daerah Jawa Timur, Malang Branch.